2003
DOI: 10.1093/ajcn/78.6.1103
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns associated with risk factors for cardiovascular disease in healthy US adults

Abstract: The identification of common dietary patterns among free-living persons is promising for characterizing high-risk groups at the US population level. The dietary patterns identified here are similar to those reported in other nonrepresentative samples and are associated with biomarkers of CVD risk, which confirms that dietary pattern analysis can be a valuable method for assessing dietary intakes when predicting CVD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
130
3
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(171 citation statements)
references
References 20 publications
29
130
3
9
Order By: Relevance
“…These findings are consistent with a body of literature. 13,29,30,33,[37][38][39][40] With regards to blood lipid levels, the Prudent pattern was inversely associated with plasma triglycerides, as previously observed. 12,41 It is somewhat surprising that the comparison across tertiles did not reveal any association between the Western pattern and plasma lipid concentrations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are consistent with a body of literature. 13,29,30,33,[37][38][39][40] With regards to blood lipid levels, the Prudent pattern was inversely associated with plasma triglycerides, as previously observed. 12,41 It is somewhat surprising that the comparison across tertiles did not reveal any association between the Western pattern and plasma lipid concentrations.…”
Section: Discussionsupporting
confidence: 81%
“…12,13,19,[29][30][31][32] The percentage of variance of dietary intake (B16%) explained by these dietary patterns was similar in magnitude to what has been reported in other studies. 22,31,[33][34][35][36] Our results suggested that both patterns are associated with obesity phenotypes and odds of obesity. First, in this study, comparisons made across tertiles of factor scores showed positive associations between Western pattern scores and anthropometric indices whereas inverse associations were observed with the Prudent pattern scores.…”
Section: Discussionmentioning
confidence: 50%
“…Similar to the present study, two major dietary patterns, a 'Western' pattern (characterised by frequent intakes of processed meat, red meat, eggs and high-fat diary products) and an 'American-healthy' pattern (characterised by frequent intakes of vegetables, salad dressings and tea), were identified in a representative sample of the adult US population (21) . A high adherence to the Western pattern was adversely related to levels of folate and markers of glucose metabolism, but not to other risk factors such as systolic blood pressure or TAG.…”
Section: Discussionsupporting
confidence: 75%
“…In the German Nutrition Survey, comprising 7124 men and women, significant differences in food consumption between regular vitamin and mineral supplement users and non-users were observed, indicating a tendency towards a healthier diet among regular users of supplements (19) . In a study by McNaughton et al (11) , dietary supplement use was positively associated with the fruit/vegetable pattern and inversely associated with a Western dietary pattern, and dietary supplement users tended to have a healthier lifestyle and diet than non-users.…”
Section: Discussionmentioning
confidence: 99%